The Role of Digital Marketing in Increasing the Income of UMKM Alam Tani Hydrofarm in Kudus - Octaviana, Donna Laili; Andni, Riyan (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. This research was conducted due to the acceleration of globalization which has driven the rapid development of digital technology, providing opportunities for businesses to enter the digital marketing market. Therefore, UMKM Alam Tani Hydrofarm can increase their income through digital marketing strategies. Purpose. The purpose of this research is to understand the role of digital marketing in increasing the income of UMKM Alam Tani Hydrofarm in Kudus Method. This study uses a qualitative descriptive approach, which aims to provide facts and data regarding the effect of digital marketing on the income of UMKM Alam Tani Hydrofarm. Results. The results of this study indicate that digital marketing implemented by UMKM Alam Tani Hydrofarm has a significant impact. These UMKM actors can continue to develop their business while meeting consumer needs through digital marketing strategies. The transition to purchasing through digital marketing will also facilitate market expansion for UMKM. Current technological developments optimize the potential of UMKM and promote sustainable growth. Social media and e-commerce platforms are important means of increasing UMKM sales. Conclusion. Through analysis of the research results and discussions presented above, it can be concluded that Micro, Small and Medium Enterprises (MSMEs) play an important role in expanding employment opportunities and act as a driving force amidst the slowdown in the Indonesian economy. Apart from that, MSMEs also need to adopt innovation in utilizing digital technology to attract more consumers, which will have an impact on increasing product demand. The marketing strategy used needs to always be updated according to developing trends in society.